2012
DOI: 10.1097/ccm.0b013e318236f473
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for adverse drug events in critically ill patients*

Abstract: Objectives An evaluation of risk factors for adverse drug events in critically ill patients has not been previously studied. The purpose of this original study was to determine risk factors for adverse drug events in critically ill adult patients. Design This retrospective case-control study includes patients who were admitted to the intensive care unit during a 7.5-yr period. Setting Academic medical center with 647 beds that contains approximately 120 intensive care unit beds. Patients Patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 26 publications
4
77
0
14
Order By: Relevance
“…The large number of pDDIs between drugs prescribed to ICU patients has been documented by several studies (Smithburger, Kane-Gill, Seybert, 2012;Rivkin, Yin, 2011;Kane-Gill et al, 2012). A recent study conducted in the USA showed that 46.3% of ICU prescriptions included pDDIs (Smithburger, Kane-Gill, Seybert, 2012), while Brazilian studies have reported a prevalence of 67% or 70% (Hammes et al, 2008;Moreira, Cassiani, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The large number of pDDIs between drugs prescribed to ICU patients has been documented by several studies (Smithburger, Kane-Gill, Seybert, 2012;Rivkin, Yin, 2011;Kane-Gill et al, 2012). A recent study conducted in the USA showed that 46.3% of ICU prescriptions included pDDIs (Smithburger, Kane-Gill, Seybert, 2012), while Brazilian studies have reported a prevalence of 67% or 70% (Hammes et al, 2008;Moreira, Cassiani, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these risk factors, the acuity of illness of patients in the ICU may confer a predisposition for ADEs [Classen et al 1997;Sikdar et al 2012;Nebeker et al 2005;Smith et al 2012;Kane-Gill et al 2012;Barr et al 2013]. As such, close monitoring of medications in the ICU is imperative [Kane-Gill et al 2012;Barr et al 2013;Drew et al 2004;Pinsky, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The intensive care unit (ICU) setting imparts a particularly high risk of ADEs, as patients are typically severely ill and often require complex medications in the setting of altered pharmacokinetics [Classen et al 1997;Nebeker et al 2005;Smith et al 2012]. Numerous risk factors for ADEs have been identified in critically ill patients such as kidney injury, thrombocytopenia and use of intravenous medications [Kane-Gill et al 2012]. In addition to these risk factors, the acuity of illness of patients in the ICU may confer a predisposition for ADEs [Classen et al 1997;Sikdar et al 2012;Nebeker et al 2005;Smith et al 2012;Kane-Gill et al 2012;Barr et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao tipo de tratamento, estudo também identificou o tratamento de emergência (clínico ou cirúrgico) em maior risco de EA pela necessidade do tratamento com medicamento intravenoso 61 . Além disso, os pacientes da UTI, principalmente quando submetidos a procedimentos cirúrgicos, apresentam maior número de dispositivos necessários a assistência e itens na prescrição medicamentosa, o que aumentam as chances de ocorrência de EA, como a infecção associada a assistência causada pela quebra de protocolos assistenciais ou mesmo a retirada não programada dos dispositivos 4,16 .…”
Section: Associação Dos Ea Moderado/grave Com As Variáveis Biossociaiunclassified
“…Além disso, os pacientes da UTI, principalmente quando submetidos a procedimentos cirúrgicos, apresentam maior número de dispositivos necessários a assistência e itens na prescrição medicamentosa, o que aumentam as chances de ocorrência de EA, como a infecção associada a assistência causada pela quebra de protocolos assistenciais ou mesmo a retirada não programada dos dispositivos 4,16 . A literatura mostra que o paciente internado na UTI apresenta maior chance de sofrer EA 54,61,67 .…”
Section: Associação Dos Ea Moderado/grave Com As Variáveis Biossociaiunclassified